PENGARUH MODAL, BAHAN BAKU, DAN TENAGA KERJA TERHADAP PENGEMBANGAN USAHA KELOMPOK TANI LESTARI COKLAT DESA BETAK KECAMATAN KALIDAWIR KABUPATEN TULUNGAGUNG - Fitriyani, Shela; Sari, Citra Mulya (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This research aims to change the behavior of the farmer groups by increasing business for rural farming communities and increasing family welfare and income by choosing sustainable cocoa farming because sustainable cocoa farmer groups not only plant and harvest cocoa beans but also process the cocoa beans to become several products. Thus, to add economic value from raw goods to finished goods, there must be factors that influence the development of a sustainable chocolate business. The purpose of this study was to analyze the effect of capital, raw materials, and labor on the business development of the Cocoa Sustainable Farmers Group in Betak Village, Kalidawir District, Tulungagung Regency. This study uses a quantitative approach, which is associative research. The data analysis technique used is the method of statistical analysis using the SPSS program to assist in the process of multiple linear regression analysis. The results showed that 1) capital, raw materials, and labor simultaneously had a significant effect on business development; 2) capital partially had a significant effect on business development; 3) raw materials partially had a significant effect on business development; and 4) labor partially had a significant effect on business development. Keywords: Capital; Raw Materials; Labor; Business Development